Photovoice for mobilizing insights on human well-being in complex social-ecological systems: case studies from Kenya and South Africa - Masterson, Vanessa A.; Mahajan, Shauna L.; Tengö, Maria (Ecology and society, 2018)
The value of diverse perspectives in social-ecological systems research and transdisciplinarity is well recognized. Human well-being and how it is derived from dynamic ecosystems is one area where local knowledge and perspectives are critical for designing interventions for sustainable pathways out of poverty. However, to realize the potential to enrich the understanding of complex dynamics for sustainability, there is a need for methods that engage holistic ways of perceiving human-nature interactions from multiple worldviews that also acknowledge inequalities between scientific and other forms of knowledge. To date, photovoice has been used to elicit local knowledge and perspectives about ecosystem changes and ecosystem services. We expand this to explore the utility of the method for facilitating the mobilization of plural insights on human well-being, which is subject to complex social-ecological dynamics, and its role in processes for coproduction of knowledge that acknowledges the need for equity and usefulness for all actors. Drawing on two cases, one in community-based marine protected areas in Kenya and one dealing with agricultural decline and rural-urban migration in South Africa, we demonstrate two modes of application of photovoice: as a scoping exercise and as a deep learning tool. The studies descriptively illustrate how photovoice can depict the hidden and often neglected intangible connections to ecosystems, plural and disaggregated perceptions of complex social-ecological dynamics, and issues of access and distribution of ecosystem benefits. The studies also show how photovoice can encourage equitable participation of nonacademic actors in research processes and in particular contribute to mobilization of knowledge and translation of knowledge across knowledge systems. We discuss how local perspectives may be further recognized and incorporated in transdisciplinary research and reflect on the practical and ethical challenges posed by using photographs in participatory research on social-ecological systems.